Esterification catalyst, preparation method thereof and application of esterification catalyst in methyl methacrylate synthesis reaction

By using an esterification catalyst composed of composite support and silicotungstic acid, the problem of low conversion and yield in methyl methacrylate production is solved, and efficient catalytic effect and good heat resistance are achieved.

CN119793523APending Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311307994.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the production process of methyl methacrylate, the conversion rate of methacrylate is not high, the yield of methyl methacrylate is low, and traditional catalysts have problems such as poor heat resistance, small specific surface area, and easy swelling.

Method used

An esterification catalyst composed of a composite support and silicotungstenic acid is used, which includes SSZ-13 molecular sieve and alumina. The silicotungstenic acid is supported on the composite support and the catalyst is prepared by drying and calcining treatment.

Benefits of technology

It improves the conversion rate of methacrylic acid and the selectivity of methyl methacrylate, has stable catalyst structure, good high temperature resistance, mild process conditions, and is easy to control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793523A_ABST
    Figure CN119793523A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fine chemical engineering, and discloses an esterification catalyst, a preparation method thereof and application of the esterification catalyst in methyl methacrylate synthesis reaction. The esterification catalyst comprises a composite carrier and silicotungstic acid, and based on the total weight of the esterification catalyst, the content of the composite carrier is 55-85 wt%, and the content of the silicotungstic acid is 15-45 wt%; the composite carrier comprises an SSZ-13 molecular sieve and aluminum oxide, and based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 50-80 wt%, and the content of the aluminum oxide is 20-50 wt%. The esterification catalyst is used for a methacrylic acid esterification reaction, and higher methacrylic acid conversion rate and methyl methacrylate selectivity can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fine chemicals, and in particular to an esterification catalyst and a preparation method thereof, as well as application of the catalyst in a methyl methacrylate synthesis reaction. Background Art

[0002] As an important type of organic chemical product and organic chemical raw material, the industrial production level and production capacity of methyl methacrylate (MMA) have an important impact on the development of my country's chemical industry. MMA is mainly used in industries such as organic glass (PMMA), coatings, textiles, adhesives, leather, papermaking, floor polishing, unsaturated resin modification, advanced methacrylate esters, wood impregnation agents, printing and dyeing auxiliaries, and plasticizers for plastics. In recent years, the demand for MMA polymers, profiles, plates, coatings, emulsions, etc. has increased at home and abroad, and the application fields are constantly expanding, which has promoted the rapid development of the MMA industry. At present, the domestic production technology of methyl methacrylate is still in its infancy. The development of esterification catalysts and supporting processes with independent intellectual property rights is a development demand faced by my country's MMA production industry.

[0003] Esterification catalyst is the core technology of MMA production. For the esterification reaction of methacrylic acid and methanol, the traditional production process using inorganic acids such as sulfuric acid, phosphoric acid, and boric acid as catalysts has been gradually eliminated. Organic acids such as p-toluenesulfonic acid as catalysts also have the disadvantages of serious environmental pollution, low selectivity, and difficult product separation. In comparison, esterification catalysts for multiphase reactions are currently a relatively active research field. In the latest reports, researchers have continuously tried to use acidic resins, organic tin compounds, rare earth solid superacids, silicotungstic acid and other catalysts in the synthesis of carboxylic esters, and have achieved meaningful experimental results. At present, acidic cation exchange resins are widely used in industry for the production of methyl methacrylate. Cation exchange resins show advantages such as good stability, high selectivity, low cost, and easy separation in esterification reactions. However, the cation exchange resin itself has poor heat resistance (generally it will decompose at temperatures not exceeding 250°C), small specific surface area and pore volume, and cation exchange resins are easy to swell. As an esterification catalyst, the reaction activity is poor and the ester yield is low. Silicotungstic acid catalysts are valued for their high activity, good selectivity and mild reaction conditions, but some silicotungstic acids have a certain solubility in organic solvents, making it difficult to separate the products. In order to solve this problem, researchers loaded silicotungstic acid on carriers such as alumina or silicon oxide to prepare supported silicotungstic acid catalysts for the esterification reaction of methacrylic acid. With the increasing demand for MMA, the use of green and environmentally friendly processes to synthesize methyl methacrylate has broad prospects. At present, solid-supported esterification catalysts are receiving more and more attention in the synthesis of methyl methacrylate. For researchers, developing esterification catalysts with excellent performance, improving reaction efficiency and inhibiting the formation of by-products are important future work directions. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low methacrylic acid conversion rate and low methyl methacrylate yield in the current methyl methacrylate production process, and to provide an esterification catalyst and a preparation method thereof, as well as application in the methyl methacrylate synthesis reaction. The esterification catalyst is used in the methacrylic acid esterification reaction to obtain a higher methacrylic acid conversion rate and methyl methacrylate selectivity.

[0005] In order to achieve the above object, the first aspect of the present invention provides an esterification catalyst, wherein the esterification catalyst comprises a composite carrier and silicotungstic acid, based on the total weight of the esterification catalyst, the content of the composite carrier is 55-85% by weight, and the content of the silicotungstic acid is 15-45% by weight;

[0006] The composite carrier comprises SSZ-13 molecular sieve and alumina. Based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 50-80% by weight, and the content of the alumina is 20-50% by weight.

[0007] The second aspect of the present invention provides a method for preparing the aforementioned esterification catalyst, wherein the preparation method comprises:

[0008] The composite carrier and the aqueous solution of silicotungstic acid are mixed and contacted to react, and then the solvent water is removed to obtain a solid product; and the solid product is dried and calcined to obtain an esterification catalyst.

[0009] A third aspect of the present invention provides an application of the aforementioned esterification catalyst in a methyl methacrylate synthesis reaction, wherein the application comprises: simultaneously contacting methacrylic acid and methanol with a catalyst, wherein the catalyst is the aforementioned esterification catalyst.

[0010] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0011] 1. The esterification catalyst provided by the present invention has a stable structure, good high temperature resistance, and does not deform or swell during the reaction.

[0012] 2. The raw materials of the esterification catalyst provided by the present invention are easily available, the preparation method is simple, the conditions are easy to control, the preparation process is environmentally friendly, and the product has good reproducibility.

[0013] 3. When the esterification catalyst provided by the present invention is used in the synthesis reaction of methyl methacrylate, the process conditions are mild and the requirements for the reaction device are not high.

[0014] 4. When the catalyst provided by the present invention is used for methacrylic acid esterification reaction, the methacrylic acid conversion rate is high and the methyl methacrylate selectivity is high.

[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0017] Figure 1 is the XRD spectrum of the composite carrier A prepared in Example 1;

[0018] Figure 2 is a pore size distribution diagram of the composite carrier A prepared in Example 1;

[0019] Figure 3 This is the pore size distribution diagram of the esterification catalyst A prepared in Example 1. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] As mentioned above, the first aspect of the present invention provides an esterification catalyst, wherein the esterification catalyst comprises a composite carrier and silicotungstic acid, and based on the total weight of the esterification catalyst, the content of the composite carrier is 55-85% by weight, and the content of the silicotungstic acid is 15-45% by weight;

[0022] The composite carrier comprises SSZ-13 molecular sieve and alumina. Based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 50-80% by weight, and the content of the alumina is 20-50% by weight.

[0023] The inventors of the present invention have found that in the prior art, the esterification catalysts used to produce methyl methacrylate are divided into two categories: homogeneous and heterogeneous. Among them, homogeneous catalysts mainly include inorganic acid solutions and organic acids, and heterogeneous catalysts mainly include solid acids and cation exchange resins. The advantages of homogeneous catalysts are low price and good catalytic activity, but they are gradually eliminated due to defects such as difficulty in separating products from catalysts, more side reactions, and easy corrosion of equipment. Although solid acid esterification catalysts solve the problems of difficult product separation and serious equipment corrosion, they are rarely used in industrial production due to disadvantages such as poor catalytic activity, high reaction temperature, and low product selectivity. Compared with the above catalysts, the production of methyl methacrylate using acidic cation exchange resins as esterification catalysts is the main process for industrial applications. Resin catalysts have the advantages of high selectivity, low cost and easy separation, but the yield of methyl methacrylate is low during the esterification reaction of methyl methacrylate, and the high temperature resistance is also poor. Resin is an organic polymer material, which is easy to swell in organic solvents, easy to deform or even decompose in high temperature environments, which is the main reason for the poor temperature resistance of resin catalysts. Developing a new solid catalyst system to make up for the performance defects of resin catalysts is a good way to solve the problem. Silicotungstic acid is a type of multi-nuclear complex containing oxygen bridges, which has strong acidity and is suitable for use as an esterification catalyst. Moreover, silicotungstic heteropoly acid has a Keggin structure, which has high catalytic activity, good selectivity, mild reaction conditions and simple process flow when catalyzing esterification reactions. However, pure silicotungstic acid has a small specific surface area, is easily soluble in polar solvents, and is difficult to recycle and reuse, so it cannot be used as a heterogeneous catalyst. In catalytic theory, people have reached a consensus on the view of active centers, and believe that the proximity of molecules to active centers is a key step. Therefore, it is necessary to find a suitable carrier to effectively disperse the heteropoly acid and maximize its catalytic effect. In view of the above reasons, supported silicotungstic acid catalysts are likely to become esterification catalysts with excellent performance. SSZ-13 molecular sieves have a certain pore structure and surface acidity, which are suitable for catalyzing the esterification reaction of small molecules. However, the pore size of this type of molecular sieve is small, which may inhibit the diffusion of large molecular products during the reaction; and the number of acidic sites on the surface of SSZ-13 molecular sieve is small, and the efficiency of catalytic esterification reaction is low, making it unsuitable to be directly used as a catalyst to catalyze the esterification reaction of methacrylic acid.

[0024] The inventors of the present invention found in the process of developing esterification catalysts that if SSZ-13 molecular sieve is compounded with aluminum-containing materials with good viscosity, a composite carrier can be prepared by appropriate molding means. The carrier is an inorganic structure, not only will not swell and deform in organic solvents, but also has good temperature resistance. After loading silicotungstic acid on the composite carrier, an esterification catalyst with good mechanical strength can be obtained. The catalyst can show good catalytic activity and methyl methacrylate selectivity when used in methacrylic acid esterification reaction.

[0025] According to the present invention, preferably, based on the total weight of the esterification catalyst, the content of the composite carrier is 60-80% by weight, and the content of the silicotungstic acid is 20-40% by weight; more preferably, based on the total weight of the esterification catalyst, the content of the composite carrier is 65-75% by weight, and the content of the silicotungstic acid is 25-35% by weight. In the present invention, the use of the above-mentioned specific content of the composite carrier and the content of silicotungstic acid can make the prepared catalyst have better catalytic activity and ester selectivity when used in the methyl methacrylate synthesis reaction.

[0026] According to the present invention, preferably, based on the total weight of the composite support, the content of the SSZ-13 molecular sieve is 55-75% by weight, and the content of the alumina is 25-45% by weight; more preferably, based on the total weight of the composite support, the content of the SSZ-13 molecular sieve is 60-70% by weight, and the content of the alumina is 30-40% by weight. In the present invention, the use of a composite support having the above-mentioned specific parameters can enable the prepared catalyst to have better catalytic activity and ester selectivity when used in an esterification reaction.

[0027] According to the present invention, the specific surface area of ​​the composite carrier is 460-530m 2 / g, and a pore volume of 0.36-0.45 ml / g; preferably, the specific surface area of ​​the composite carrier is 470-520 m 2 / g, and a pore volume of 0.38-0.44 ml / g; more preferably, the specific surface area of ​​the composite carrier is 480-505 m 2 / g, and the pore volume is 0.39-0.42ml / g.

[0028] According to the present invention, the shape of the composite carrier is not limited, and can be a bar, a sphere, a cylinder, a toothed sphere, a cloverleaf shape or a hollow cylinder.

[0029] According to the present invention, the preparation method of the composite carrier is as follows:

[0030] Alumina precursor, SSZ-13 molecular sieve, acidic aqueous solution and extrusion aid are mixed and subjected to an extrusion molding process to obtain a composite carrier precursor; the composite carrier precursor is then dried and calcined to obtain a composite carrier.

[0031] According to the present invention, the alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite, preferably pseudo-boehmite. In the present invention, the alumina precursor can be obtained commercially. Specifically, the pseudo-boehmite is preferably: pseudo-boehmite powder with model number P-DF-07-LSi (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​249m 2 / g, pore volume of 0.82ml / g), pseudo-boehmite powder of model P-DF-09-LSi (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​286m 2 / g, pore volume 1.08ml / g), German imported pseudo-boehmite powder of model SB (purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of ​​241m 2 / g, pore volume of 0.53ml / g), macroporous pseudo-boehmite powder of model PB-0101 (produced by Zibo Hengqi Powder New Material Co., Ltd.) and pseudo-boehmite powder of model PB-0104 (produced by Zibo Hengqi Powder New Material Co., Ltd., with a specific surface area of ​​327m 2 / g, pore volume is 1.02ml / g).

[0032] According to the present invention, the SiO 2 / Al 2 O 3 The molar ratio is 10-40, preferably 20-30.

[0033] According to the present invention, the acidic aqueous solution can be an organic acid aqueous solution or an inorganic acid aqueous solution, preferably one or more of a formic acid aqueous solution, an acetic acid aqueous solution, a citric acid aqueous solution, a nitric acid aqueous solution and a hydrochloric acid aqueous solution, more preferably one or more of a nitric acid aqueous solution, an acetic acid aqueous solution and a citric acid aqueous solution; the mass concentration of the acidic aqueous solution can be 1-20%, preferably 2-10%.

[0034] According to the present invention, the extrusion aid is selected from one or more of sesbania powder, polyethylene glycol, polyvinyl alcohol, polyacrylamide and cellulose.

[0035] According to the present invention, the weight ratio of the alumina precursor: the SSZ-13 molecular sieve: the extrusion aid: the acidic aqueous solution is 1: (0.5-3): (0.05-0.5): (0.5-5), preferably 1: (0.8-2.5): (0.1-0.3): (1-2).

[0036] According to the present invention, the drying conditions may include: a temperature of 70-150° C. and a time of 3-24 hours.

[0037] According to the present invention, the calcination conditions may include: a temperature of 400-700° C. and a time of 2-30 hours.

[0038] According to the present invention, the specific surface area of ​​the esterification catalyst is 250-450m 2 / g, and a pore volume of 0.25-0.31 ml / g; preferably, the specific surface area of ​​the esterification catalyst is 280-410 m 2 / g, and a pore volume of 0.26-0.3 ml / g; more preferably, the specific surface area of ​​the esterification catalyst is 315-380 m 2 / g, and the pore volume is 0.27-0.29ml / g.

[0039] The second aspect of the present invention provides a method for preparing the aforementioned esterification catalyst, wherein the preparation method comprises:

[0040] The composite carrier and the aqueous solution of silicotungstic acid are mixed and contacted to react, and then the solvent water is removed to obtain a solid product; and the solid product is dried and calcined to obtain an esterification catalyst.

[0041] According to the present invention, the concentration of the aqueous solution of silicotungstic acid is 2-30%, preferably 5-20%.

[0042] According to the present invention, the weight ratio of the composite carrier to the aqueous solution of silicotungstic acid is 1:(1-20), preferably 1:(2-10).

[0043] According to the present invention, the conditions for the contact reaction between the composite support and the aqueous solution of silicotungstic acid include: the reaction temperature can be 30-120°C, preferably 40-90°C; the time can be 0.5-20h, preferably 2-10h. Preferably, in order to achieve a better contact reaction effect, the composite support and the aqueous solution of silicotungstic acid can be rapidly stirred or ultrasonic means can be used to improve the contact reaction efficiency during the contact reaction.

[0044] According to the present invention, there is no special requirement for the method of removing the solvent water. For example, the solvent water can be removed by using a rotary evaporator or a heating and stirring method to obtain a solid product.

[0045] According to the present invention, the conditions for drying the solid product are preferably: drying temperature 80-130° C., and drying time 3-20 hours.

[0046] According to the present invention, the conditions for calcining the solid product include: the temperature can be 350-550° C., preferably 400-500° C.; the time can be 2-16 hours, preferably 4-10 hours.

[0047] A third aspect of the present invention provides an application of the aforementioned esterification catalyst in a methyl methacrylate synthesis reaction, wherein the application comprises: simultaneously contacting methacrylic acid and methanol with a catalyst, wherein the catalyst is the aforementioned esterification catalyst.

[0048] According to the present invention, the contact conditions of methacrylic acid and methanol with the catalyst include: the contact temperature is 40-150°C, preferably 60-120°C; the contact pressure is 0.01-5MPa, preferably 0.1-3Mpa; the mass space velocity of methacrylic acid is 0.01-30h -1 , preferably 0.1-10h -1 ; The mass space velocity of methanol is 0.01-50h -1 , preferably 0.1-30h -1 .

[0049] The present invention will be described in detail below through examples.

[0050] The XRD test of the sample was carried out on an X'Pert MPD X-ray powder diffractometer of Philips Company of the Netherlands, with a Cu Kα target and a scanning range of 2θ=5-90°.

[0051] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The samples were vacuum degassed at 350°C for 4 hours before measurement. The sample specific surface area was calculated using the BET method, and the pore volume was calculated using the BJH model. The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0052] The rotary evaporator was produced by IKA of Germany, model RV10 digital.

[0053] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0054] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0055] Pseudo-boehmite powders of model numbers P-DF-07-LSi and P-DF-09-LSi were purchased from Shandong Aluminum Co., Ltd.; Pseudo-boehmite powders of model number SB imported from Germany were purchased from Beijing Asia Pacific Aowa Chemical Additives Co., Ltd.; Macroporous pseudo-boehmite powders of model numbers PB-0101 and PB-0104 were purchased from Shandong Zibo Hengqi Powder New Materials Co., Ltd.; SiO 2 / Al 2 O 3SSZ-13 molecular sieve with a molar ratio of 20 was purchased from Nanjing Jicang Nanotechnology Co., Ltd.; SiO 2 / Al 2 O 3 SSZ-13 molecular sieve with a molar ratio of 30 was purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd. The reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.

[0056] Example 1

[0057] (1) Preparation of composite carrier

[0058] 50g of P-DF-09-LSi pseudo-boehmite powder and 65g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 = 20), 65g of 5% dilute nitric acid and 6g of sesbania powder were mixed evenly, extruded into strips, and a strip extrusion die with a pore size of 2.5mm was selected. The formed product was dried at 110°C for 10h, and then calcined at 600°C for 12h to obtain a composite carrier A.

[0059] Based on the total weight of the composite carrier A, the content of the SSZ-13 molecular sieve is 65% by weight, and the content of the alumina is 35% by weight.

[0060] The specific surface area of ​​composite carrier A is 494m 2 / g, and the pore volume is 0.4ml / g.

[0061] Figure 1 is the XRD spectrum of composite carrier A. Figure 1 It is shown that the x-ray diffraction angles of the sample are mainly: 2θ = 9.5°, 14.1°, 16.2°, 17.9°, 20.7°, 25.0°, 30.7°, 36.9°, 39.5°, 45.9° and 66.9°. Among them, the seven diffraction signals at 2θ = 9.5°, 14.1°, 16.2°, 17.9°, 20.7°, 25.0° and 30.7° are consistent with the CHA structure diffraction spectrum of SSZ-13 molecular sieve, indicating that the SSZ-13 molecular sieve crystal phase has not changed significantly during the preparation of composite carrier A, and still maintains a good zeolite molecular sieve framework structure. The four diffraction signals at 2θ = 36.9°, 39.5°, 45.9° and 66.9° are consistent with the γ-Al 2 O 3 The diffraction spectra are consistent, indicating that the composite support A is calcined at 600℃ during the preparation process, and the pseudo-boehmite is mainly γ-Al 2 O 3 Crystalline phase exists.

[0062] Figure 2 is the pore size distribution diagram of composite carrier A. Figure 2 The above shows that the sample has an obvious double-pore structure, with double pore diameters of 0.4nm and 7nm respectively. Among them, the micropores with a pore size of 0.4nm are provided by SSZ-13 molecular sieve, and the mesopores with an average pore size of 7nm are provided by γ-Al 2 O 3 Since SSZ-13 molecular sieve has a regular topological structure, the pore size distribution of 0.4nm is relatively concentrated; and the γ-Al obtained by calcining pseudo-boehmite 2 O 3 The pore structure is disordered in both short and long ranges, so the pore size distribution is wide.

[0063] (2) Preparation of esterification catalyst

[0064] 70g of composite carrier A was mixed with 300g of 10% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed by rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst A.

[0065] In terms of weight percentage, the composition of the esterification catalyst A is as follows: the content of the composite carrier A is 70%, and the content of silicotungstic acid is 30%.

[0066] The specific surface area of ​​esterification catalyst A is 346 m 2 / g, and the pore volume is 0.28mL / g.

[0067] Figure 3 is the pore size distribution diagram of esterification catalyst A. Figure 3 The above shows that the sample has an obvious double-pore structure, with double pore diameters of 0.35nm and 5.4nm respectively. Among them, the micropores with a pore size of 0.35nm are provided by SSZ-13 molecular sieve, and the mesopores with an average pore size of 5.4nm are provided by γ-Al 2 O 3 The loaded silicotungstic acid will cause partial blockage of micropores and mesopores, resulting in that the double pore size of the esterification catalyst is smaller than the pore size of the composite carrier A.

[0068] (3) Catalyst reaction performance evaluation

[0069] The esterification performance of the catalyst was evaluated in a fixed bed reactor. 5 g of esterification catalyst A was loaded into a stainless steel fixed bed reactor with an inner diameter of 8 mm, the reaction temperature was 95°C, the reaction pressure was 0.5 MPa, and the weight space velocity of methacrylic acid was 1 h -1 , the weight space velocity of methanol is 2.7h -1The reaction time was 20 hours. After cooling, the product was analyzed by an Agilent 7890A gas chromatograph equipped with a FFAP capillary column and a hydrogen flame detector (FID), using programmed temperature and correction factors for quantitative analysis. The methacrylic acid conversion rate was 95.1%, and the selectivity of methyl methacrylate was 99.7%.

[0070] Example 2

[0071] (1) Preparation of composite carrier

[0072] 43g of PB-0101 macroporous pseudo-boehmite powder, 70g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 =30), 75g of 10% acetic acid aqueous solution and 8g of polyethylene glycol are mixed, transferred to a kneader and stirred to mix evenly. The kneading temperature is 35°C, the main shaft speed of the kneader is 150r / min, and the kneading time is 1h. The mixed raw materials are placed in the hopper of a micro-ball making machine, and a strip extrusion mold with an aperture of 2.5mm is selected. The strip extrusion speed is adjusted to 5m / min, and the cutting speed is 2000 grains / minute. The raw materials are extruded into strips and extruded and cut into small round particles. The above-mentioned small round particles are placed in a micro-pellet shaping machine for shaping. The shaping conditions are as follows: the rounding time is 0.5 minutes / time, the rounding number is 2 times, and the sample chamber speed is 500r / min. The standard spherical raw material balls obtained after shaping are placed in a micro-pellet screening machine to screen out spherical precursors with a size of 2.5mm. The spherical precursor is dried at 110°C for 8h, and then calcined at 700°C for 12h to obtain a composite carrier B.

[0073] Based on the total weight of the composite carrier B, the content of the SSZ-13 molecular sieve is 70% by weight, and the content of the alumina is 30% by weight.

[0074] The specific surface area of ​​composite carrier B is 505m 2 / g, the pore volume is 0.39ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 9.5nm.

[0075] (2) Preparation of esterification catalyst

[0076] 75g of composite carrier B was mixed with 500g of 5% silicotungstic acid aqueous solution, and stirred at 90°C for 2h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was washed with distilled water 4 times, dried at 130°C for 5h, and then calcined at 400°C for 10h to obtain esterification catalyst B.

[0077] Based on the total weight of the esterification catalyst B, the content of the composite carrier B was 75% by weight, and the content of silicotungstic acid was 25% by weight.

[0078] The specific surface area of ​​esterification catalyst B is 380m 2 / g, the pore volume is 0.29mL / g, the micropore diameter is 0.36nm, and the mesopore diameter is 8.2nm.

[0079] (3) Catalyst reaction performance evaluation

[0080] The esterification performance of catalyst B was tested according to the method of step (3) in Example 1. The conversion rate of methacrylic acid was 94.8%, and the selectivity of methyl methacrylate was 99.8%.

[0081] Example 3

[0082] (1) Preparation of composite carrier

[0083] 53g of SB pseudo-boehmite powder imported from Germany, 60g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 = 20), 80g of 15% citric acid aqueous solution and 15g of cellulose were mixed evenly, extruded into strips, cut and shaped into toothed balls, dried at 110°C for 12h, and then calcined at 550°C for 15h to obtain a composite carrier C.

[0084] Based on the total weight of the composite carrier C, the content of the SSZ-13 molecular sieve is 60% by weight, and the content of the alumina is 40% by weight.

[0085] The specific surface area of ​​composite carrier C is 480m 2 / g, the pore volume is 0.42ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 6.7nm.

[0086] (2) Preparation of esterification catalyst

[0087] 65g of composite carrier C was mixed with 175g of 20% silicotungstic acid aqueous solution, and stirred at 60°C for 8h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was washed with distilled water 4 times, dried at 80°C for 20h, and then calcined at 500°C for 4h to obtain esterification catalyst C.

[0088] Based on the total weight of the esterification catalyst C, the content of the composite carrier C was 65% by weight, and the content of silicotungstic acid was 35% by weight.

[0089] The specific surface area of ​​esterification catalyst C is 315m 2 / g, the pore volume is 0.27mL / g, the micropore diameter is 0.34nm, and the mesopore diameter is 5nm.

[0090] (3) Catalyst reaction performance evaluation

[0091] The esterification performance of catalyst C was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 94.5%, and the selectivity of methyl methacrylate was 99.6%.

[0092] Example 4

[0093] (1) Preparation of composite carrier

[0094] 36g of P-DF-07-LSi pseudo-boehmite powder, 75g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 = 20), 60g of 8% dilute nitric acid and 4g of polyvinyl alcohol were mixed evenly, extruded into strips, and a strip extrusion die with a pore size of 2mm was selected. The formed product was dried at 110°C for 10h, and then calcined at 600°C for 12h to obtain a composite carrier D.

[0095] Based on the total weight of the composite carrier D, the content of the SSZ-13 molecular sieve is 75% by weight, and the content of the alumina is 25% by weight.

[0096] The specific surface area of ​​composite carrier D is 520 m 2 / g, the pore volume is 0.38ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 8.7nm.

[0097] (2) Preparation of esterification catalyst

[0098] 80g of composite carrier D was mixed with 200g of 10% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed by rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst D.

[0099] In terms of weight percentage, the composition of the esterification catalyst D is as follows: the content of the composite carrier D is 80% and the content of silicotungstic acid is 20%.

[0100] The specific surface area of ​​esterification catalyst D is 410 m 2 / g, the pore volume is 0.30mL / g, the micropore diameter is 0.37nm, and the mesopore diameter is 7.2nm.

[0101] (3) Catalyst reaction performance evaluation

[0102] The catalytic performance of Catalyst D was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 93.7%, and the selectivity of methyl methacrylate was 99.2%.

[0103] Example 5

[0104] (1) Preparation of composite carrier

[0105] 64g of PB-0104 macroporous pseudo-boehmite powder, 55g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 =30), 82g of 12% acetic acid aqueous solution and 7g of sesbania powder were uniformly mixed, and a strip extrusion die with a pore size of 2mm was selected, and the strips were extruded and cut into toothed ball shapes, dried at 110°C for 12h, and then calcined at 550°C for 15h to obtain a composite carrier E.

[0106] Based on the total weight of the composite carrier E, the content of the SSZ-13 molecular sieve is 55 wt %, and the content of the alumina is 45 wt %.

[0107] The specific surface area of ​​composite carrier E is 470 m 2 / g, the pore volume is 0.44ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 7.2nm.

[0108] (2) Preparation of esterification catalyst

[0109] 60g of composite carrier E was mixed with 500g of 8% silicotungstic acid aqueous solution, and stirred at 90°C for 2h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was washed with distilled water 4 times, dried at 130°C for 5h, and then calcined at 400°C for 10h to obtain esterification catalyst E.

[0110] Based on the total weight of the esterification catalyst E, the content of the composite support E was 60% by weight, and the content of silicotungstic acid was 40% by weight.

[0111] The specific surface area of ​​esterification catalyst E is 280 m 2 / g, the pore volume is 0.26mL / g, the micropore diameter is 0.33nm, and the mesopore diameter is 5.3nm.

[0112] (3) Catalyst reaction performance evaluation

[0113] The esterification performance of catalyst E was tested according to the method of step (3) in Example 1. The methacrylic acid conversion rate was 93.4%, and the selectivity of methyl methacrylate was 99%.

[0114] Example 6

[0115] (1) Preparation of composite carrier

[0116] 27g of SB pseudo-boehmite powder imported from Germany, 80g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 = 20), 65g of 10% citric acid aqueous solution and 10g of cellulose were mixed evenly. Extruded into strips, a strip extrusion die with a pore size of 3mm was selected. The formed product was dried at 110°C for 10h, and then calcined at 600°C for 12h to obtain a composite carrier F.

[0117] Based on the total weight of the composite carrier F, the content of the SSZ-13 molecular sieve is 80% by weight, and the content of the alumina is 20% by weight.

[0118] The specific surface area of ​​composite carrier F is 530m 2 / g, the pore volume is 0.36ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 7.3nm.

[0119] (2) Preparation of esterification catalyst

[0120] 85g of composite carrier F was mixed with 100g of 15% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst F.

[0121] In terms of weight percentage, the composition of the esterification catalyst F is as follows: the content of the composite carrier F is 85%, and the content of silicotungstic acid is 15%.

[0122] The specific surface area of ​​esterification catalyst F is 450 m 2 / g, the pore volume is 0.31mL / g, the micropore diameter is 0.38nm, and the mesopore diameter is 6.7nm.

[0123] (3) Catalyst reaction performance evaluation

[0124] The catalytic performance of Catalyst F was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 91.8%, and the selectivity of methyl methacrylate was 98.7%.

[0125] Example 7

[0126] (1) Preparation of composite carrier

[0127] 72g of PB-0104 macroporous pseudo-boehmite powder, 50g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3=30), 75g of 8% acetic acid aqueous solution and 5g of sesbania powder were uniformly mixed, and a strip extrusion die with a pore size of 2mm was selected, and the strips were extruded and cut into toothed ball shapes, dried at 110°C for 12h, and then calcined at 550°C for 15h to obtain a composite carrier G.

[0128] Based on the total weight of the composite carrier G, the content of the SSZ-13 molecular sieve is 50 weight %, and the content of the alumina is 50 weight %.

[0129] The specific surface area of ​​composite carrier G is 460m 2 / g, the pore volume is 0.45ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 7.2nm.

[0130] (2) Preparation of esterification catalyst

[0131] 55g of composite carrier G was mixed with 600g of 7.5% silicotungstic acid aqueous solution, and stirred at 90°C for 2h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was washed with distilled water 4 times, dried at 130°C for 5h, and then calcined at 400°C for 10h to obtain esterification catalyst G.

[0132] Based on the total weight of the esterification catalyst G, the content of the composite carrier G was 55% by weight, and the content of silicotungstic acid was 45% by weight.

[0133] The specific surface area of ​​esterification catalyst G is 250m 2 / g, the pore volume is 0.25mL / g, the micropore diameter is 0.31nm, and the mesopore diameter is 5nm.

[0134] (3) Catalyst reaction performance evaluation

[0135] The esterification performance of catalyst G was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 91.5%, and the selectivity of methyl methacrylate was 98.6%.

[0136] Comparative Example 1

[0137] The composite carrier A was prepared according to the method of step (1) in Example 1.

[0138] The preparation conditions of the esterification catalyst in step (2) of Example 1 were changed to obtain esterification catalyst D1. The specific operation process is as follows:

[0139] 38g of composite carrier A was mixed with 620g of 10% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst D1.

[0140] Based on the total weight of the esterification catalyst D1, the content of the composite support A was 38% by weight, and the content of silicotungstic acid was 62% by weight.

[0141] The specific surface area of ​​esterification catalyst D1 is 188m 2 / g, the pore volume is 0.15mL / g, the micropore diameter is 0.26nm, and the mesopore diameter is 4.1nm.

[0142] The catalytic performance of catalyst D1 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 81.6%, and the selectivity of methyl methacrylate was 94.7%.

[0143] Comparative Example 2

[0144] The composite carrier A was prepared according to the method of step (1) in Example 1.

[0145] The preparation conditions of the esterification catalyst in step (2) of Example 1 were changed to obtain esterification catalyst D1. The specific operation process is as follows:

[0146] 93g of composite carrier A was mixed with 70g of 10% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst D2.

[0147] Based on the total weight of the esterification catalyst D2, the content of the composite support A was 93% by weight, and the content of silicotungstic acid was 7% by weight.

[0148] The specific surface area of ​​esterification catalyst D2 is 460m 2 / g, the pore volume is 0.38mL / g, the micropore diameter is 0.4nm, and the mesopore diameter is 6.7nm.

[0149] The catalytic performance of catalyst D2 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 71.5%, and the selectivity of methyl methacrylate was 92.8%.

[0150] Comparative Example 3

[0151] (1) Preparation of composite carrier

[0152] 114 g of P-DF-07-LSi pseudo-boehmite powder, 20 g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3= 20), 90g of 2% nitric acid aqueous solution and 6g of cellulose were mixed evenly. Extruded into strips, a strip extrusion die with a pore size of 2.5mm was selected. The formed product was dried at 110°C for 10h, and then calcined at 600°C for 12h to obtain a composite carrier D3.

[0153] Based on the total weight of the composite carrier D3, the content of SSZ-13 molecular sieve is 80% by weight, and the content of alumina is 20% by weight.

[0154] The specific surface area of ​​composite carrier D3 is 394m 2 / g, the pore volume is 0.54ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 8.7nm.

[0155] (2) Preparation of esterification catalyst

[0156] 60g of composite carrier D3 was mixed with 1000g of 4% silicotungstic acid aqueous solution, and stirred at 70°C for 6h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 100°C for 12h, and then calcined at 450°C for 5h to obtain esterification catalyst D3.

[0157] In terms of weight percentage, the composition of the esterification catalyst D3 is as follows: the content of the composite carrier D3 is 60%, and the content of silicotungstic acid is 40%.

[0158] The specific surface area of ​​esterification catalyst D3 is 237m 2 / g, the pore volume is 0.32mL / g, the micropore diameter is 0.36nm, and the mesopore diameter is 6.8nm.

[0159] (3) Catalyst reaction performance evaluation

[0160] The catalytic performance of catalyst D3 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 85.2%, and the selectivity of methyl methacrylate was 94.3%.

[0161] Comparative Example 4

[0162] (1) Preparation of composite carrier

[0163] 9g of PB-0104 macroporous pseudo-boehmite powder, 94g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 =30), 60g of 4% acetic acid aqueous solution and 3g of sesbania powder were uniformly mixed, and a strip extrusion die with a pore size of 2mm was selected, and the strips were extruded and cut into toothed ball shapes, dried at 110°C for 12h, and then calcined at 550°C for 15h to obtain a composite carrier D4.

[0164] Based on the total weight of the composite carrier D4, the content of the SSZ-13 molecular sieve is 94% by weight, and the content of the alumina is 6% by weight.

[0165] The specific surface area of ​​composite carrier D4 is 567m 2 / g, the pore volume is 0.32ml / g, the micropore diameter is 0.4nm, and the mesopore diameter is 7.2nm.

[0166] (2) Preparation of esterification catalyst

[0167] 78g of composite carrier D4 was mixed with 100g of 22% silicotungstic acid aqueous solution, and stirred at 90°C for 2h. After the reaction, the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was washed with distilled water 4 times, dried at 130°C for 5h, and then calcined at 400°C for 10h to obtain esterification catalyst D4.

[0168] Based on the total weight of the esterification catalyst D4, the content of the composite support D4 was 78% by weight, and the content of silicotungstic acid was 22% by weight.

[0169] The specific surface area of ​​esterification catalyst D4 is 456m 2 / g, the pore volume is 0.24mL / g, the micropore diameter is 0.36nm, and the mesopore diameter is 5.7nm.

[0170] (3) Catalyst reaction performance evaluation

[0171] The esterification performance of catalyst D4 was tested according to the method of step (3) in Example 1. The methacrylic acid conversion rate was 82.1%, and the selectivity of methyl methacrylate was 93.6%.

[0172] Comparative Example 5

[0173] Step (1) in Example 1 was eliminated, and the composite support A in step (2) in Example 1 was replaced with commercially available silicon dioxide to obtain a catalyst D5, wherein the content of the commercially available silicon dioxide was 70% by weight and the content of silicotungstic acid was 30% by weight based on the total weight of the catalyst D5.

[0174] The specific surface area of ​​esterification catalyst D5 is 173m 2 / g, the pore volume is 0.43mL / g, it has a single pore channel, and the average pore diameter is 11.4nm.

[0175] The catalytic performance of catalyst D5 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 75.4%, and the selectivity of methyl methacrylate was 95.5%.

[0176] Comparative Example 6

[0177] The composite carrier DZ6 was prepared in the same manner as step (1) in Example 1, except that: 65 g of SSZ-13 molecular sieve (SiO 2 / Al 2 O 3 =20)" was replaced by "65g ZSM-5 molecular sieve (SiO 2 / Al 2 O 3 =300)"; and based on the total weight of the composite carrier DZ6, the content of ZSM-5 molecular sieve is 65% by weight, and the content of alumina is 35% by weight.

[0178] The specific surface area of ​​the composite carrier DZ6 is 320 m 2 / g, and the pore volume is 0.35ml / g.

[0179] The esterification catalyst D6 was prepared in the same manner as the esterification catalyst in step (2) of the example, except that the "composite carrier A" was replaced by the "composite carrier DZ6".

[0180] In terms of weight percentage, the composition of the esterification catalyst D6 is as follows: the content of the composite carrier DZ6 is 70% and the content of silicotungstic acid is 30%.

[0181] The specific surface area of ​​esterification catalyst D6 is 172m 2 / g, and the pore volume is 0.23mL / g.

[0182] The esterification catalyst D6 was evaluated according to the catalyst reaction performance in step (3) of the example. The results showed that the methacrylic acid conversion was 86.7% and the selectivity of methyl methacrylate was 95%.

[0183] It can be seen from the above results that the esterification catalyst provided by the present invention can directly convert methacrylic acid and methanol into methyl methacrylate, thereby obtaining a higher methacrylic acid conversion rate and methyl methacrylate selectivity.

[0184] By comparing the data of Example 1 and Comparative Example 1, it can be seen that if the loading amount of silicotungstic acid is too high, it is not within the scope of the claims. The dispersion of the active components on the catalyst is not uniform enough, and the pores of the carrier are seriously blocked, which affects the normal progress of the reaction, resulting in low methacrylic acid conversion and methyl methacrylate selectivity.

[0185] By comparing the data of Example 1 and Comparative Example 2, it can be seen that if the loading amount of silicotungstic acid is too low, it is not within the scope of the claims. The number of active components on the catalyst is small, which will lead to low methacrylic acid conversion and methyl methacrylate selectivity.

[0186] By comparing the data of Example 1 and Comparative Example 3, it can be seen that if the content of SSZ-13 molecular sieve in the composite carrier is too high and the content of alumina is too low, it is not within the scope of the claims. Since there are too many microporous structures in the carrier, the diffusion of macromolecular reaction raw materials is hindered during the reaction, resulting in relatively low methacrylic acid conversion and methyl methacrylate selectivity.

[0187] By comparing the data of Example 1 and Comparative Example 4, it can be seen that if the content of SSZ-13 molecular sieve in the composite carrier is too low and the content of alumina is too high, it is not within the scope of the claims. The pore volume of the prepared esterification catalyst is small, which still affects the diffusion during the reaction, thereby resulting in low methacrylic acid conversion and methyl methacrylate selectivity.

[0188] By comparing the data of Example 1 and Comparative Example 5, it can be seen that if commercially available silica is used instead of the composite carrier to prepare the esterification catalyst, the methacrylic acid conversion rate and methyl methacrylate selectivity of the catalyst are relatively low due to the small specific surface area of ​​the commercially available silica and the uneven pore size.

[0189] Comparing the data of Example 1 and Comparative Example 5, it can be seen that the use of SiO 2 / Al 2 O 3 =300 ZSM-5 molecular sieve, due to the high silicon and aluminum content of ZSM-5 molecular sieve and fewer surface acid centers, the methacrylic acid conversion rate and methyl methacrylate selectivity of the catalyst are relatively low.

[0190] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An esterification catalyst, characterized in that The esterification catalyst comprises a composite carrier and silicotungstic acid, and based on the total weight of the esterification catalyst, the content of the composite carrier is 55-85% by weight, and the content of the silicotungstic acid is 15-45% by weight; The composite carrier comprises SSZ-13 molecular sieve and alumina. Based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 50-80% by weight, and the content of the alumina is 20-50% by weight.

2. The esterification catalyst according to claim 1, wherein Based on the total weight of the esterification catalyst, the content of the composite carrier is 60-80% by weight, and the content of the silicotungstic acid is 20-40% by weight; Preferably, based on the total weight of the esterification catalyst, the content of the composite carrier is 65-75% by weight, and the content of the silicotungstic acid is 25-35% by weight.

3. The esterification catalyst according to claim 1 or 2, based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 55-75% by weight, and the content of the alumina is 25-45% by weight; More preferably, based on the total weight of the composite carrier, the content of the SSZ-13 molecular sieve is 60-70% by weight, and the content of the alumina is 30-40% by weight.

4. The esterification catalyst according to any one of claims 1 to 3, wherein The specific surface area of ​​the composite carrier is 460-530m 2 / g, pore volume is 0.36-0.45ml / g; Preferably, the specific surface area of ​​the composite carrier is 470-520m 2 / g, pore volume is 0.38-0.44ml / g; More preferably, the specific surface area of ​​the composite carrier is 480-505m 2 / g, and the pore volume is 0.39-0.42ml / g.

5. The esterification catalyst according to any one of claims 1 to 4, wherein The preparation method of the composite carrier is as follows: Alumina precursor, SSZ-13 molecular sieve, acidic aqueous solution and extrusion aid are mixed and subjected to an extrusion molding process to obtain a composite carrier precursor; the composite carrier precursor is then dried and calcined to obtain a composite carrier.

6. The esterification catalyst according to claim 5, wherein The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite; And / or, the SiO2 / Al2O3 molar ratio of the SSZ-13 molecular sieve is 10-40; And / or, the mass concentration of the acidic aqueous solution is 1-20%, preferably 2-10%; And / or, the extrusion aid is selected from one or more of sesbania powder, polyethylene glycol, polyvinyl alcohol, polyacrylamide and cellulose; And / or, the weight ratio of the alumina precursor: the SSZ-13 molecular sieve: the extrusion aid: the acidic aqueous solution is 1: (0.5-3): (0.05-0.5): (0.5-5).

7. The esterification catalyst according to any one of claims 1 to 6, wherein The specific surface area of ​​the esterification catalyst is 250-450m 2 / g, pore volume is 0.25-0.31ml / g; Preferably, the specific surface area of ​​the esterification catalyst is 280-410m 2 / g, pore volume is 0.26-0.3ml / g; More preferably, the specific surface area of ​​the esterification catalyst is 315-380m 2 / g, and the pore volume is 0.27-0.29ml / g.

8. A method for preparing the esterification catalyst according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The composite carrier and the aqueous solution of silicotungstic acid are mixed and contacted to react, and then the solvent water is removed to obtain a solid product; and the solid product is dried and calcined to obtain an esterification catalyst.

9. The preparation method according to claim 8, wherein: The concentration of the aqueous solution of silicotungstic acid is 2-30%; and / or, the weight ratio of the composite carrier to the aqueous solution of silicotungstic acid is 1:(1-20); And / or, the reaction conditions include: temperature of 30-120°C, time of 0.5-20h; And / or, the calcination conditions include: temperature of 350-550° C. and time of 2-16 h.

10. Use of the esterification catalyst according to any one of claims 1 to 7 in the synthesis reaction of methyl methacrylate, wherein: The application comprises: contacting methacrylic acid and methanol with a catalyst at the same time, wherein the catalyst is the esterification catalyst according to any one of claims 1 to 7.

11. The use according to claim 10, wherein: The contact conditions of methacrylic acid and methanol with the catalyst include: the contact temperature is 40-150°C, preferably 60-120°C; the contact pressure is 0.01-5MPa, preferably 0.1-3Mpa; the mass space velocity of methacrylic acid is 0.01-30h -1 , preferably 0.1-10h -1 ; The mass space velocity of methanol is 0.01-50h -1 , preferably 0.1-30h -1 .

Citation Information

Patent Citations

  • Silicon tungsten, phosphorus heteropoly tungstic acid load type catalyzer used for esterification reaction, manufacturing method and application thereof

    CN101108360A

  • Spherical esterification catalyst, preparation method thereof and application of spherical esterification catalyst in acetic ester synthesis reaction

    CN115487856A

  • Spherical esterification catalyst as well as preparation method and application thereof in synthesis reaction of n-butyl acetate

    CN116532137A

  • Preparation for hydrophobic solid acid catalyst

    CN1613559A

  • Preparation of alpha, beta-unsaturated carboxylic acids and esters thereof

    WO2013134385A1